Biophysical modelling of larval drift, growth and survival for the prediction of anchovy ( Engraulis encrasicolus ) recruitment in the Bay of Biscay (NE Atlantic) - GWENHAEL ALLAIN; PIERRE PETITGAS; PASCAL LAZURE; PATRICK GRELLIER (Fisheries Oceanography, 2007)
Fish recruitment is the result of the integration of small‐scale processes affecting larval survival over a season and large oceanic areas. A hydrodynamic model was used to explore and model these physical–biological interaction mechanisms and then to perform the integration from individual to population scales in order to provide recruitment predictions for fisheries management. This method was applied to the case of anchovy ( Engraulis encrasicolus ) in the Bay of Biscay (NE Atlantic). The main data available to investigate survival mechanisms were past growth (otolith) records of larvae and juveniles sampled at sea. The drift history of these individuals was reconstructed by a backtracking procedure using hydrodynamic simulations. The relationships between (real) growth variation and variations in physical parameters (estimated by hydrodynamic simulations) were explored along the individual trajectories obtained. These relationships were then used to build and adjust individual‐based growth and survival models. Thousands of virtual buoys were released in the hydrodynamic model in order to reproduce the space–time spawning dynamics. Along the buoy trajectories (representative of sub‐cohorts), the biophysical model was run to simulate growth and survival as a function of the environment encountered. The survival rate after 3 months of drift was estimated for each sub‐cohort. The sum of all these survival rates over the season constituted an annual recruitment index. This index was validated over a series of recruitment estimations. The modelling choices, model results and the potential use of the recruitment index for fisheries management are discussed.

The selection process from larval to juvenile stages of anchovy ( Engraulis encrasicolus ) in the Bay of Biscay investigated by Lagrangian simulations and comparative otolith growth - Gwenhael Allain; Pierre Petitgas; Patrick Grellier; Pascal Lazure (Fisheries Oceanography, 2003)
The relation between growth and survival was investigated using the otolith growth data collected during repeated larval surveys (May–July) and a juvenile survey (September) undertaken in 1999 on anchovy spawning and nursery grounds in the Bay of Biscay (NE Atlantic). The paper describes the methodology for reading the larval and juvenile otoliths, for reconstructing the correspondence in space and time between juveniles and larvae using Lagrangian simulations, and for comparing the otolith growth rates among the reconstructed sub‐cohorts. Virtual buoys were released weekly on the grid of a three‐dimensional hydrodynamic model and their trajectories were tracked. The origin of an individual was determined by selecting the trajectory beginning on its hatching week and ending at the minimum distance of its sampling location on the sampling date. Larvae and juveniles with the same spatio‐temporal origin were selected and supposed to belong to the same sub‐cohorts. The surviving juveniles showed faster growth rates during their larval period than the pool of larvae they were estimated to originate from, which supports the idea of growth‐selective survival. Alternative interpretations (transport and gear selectivity) are discussed. Variations in otolith growth pattern also suggest a higher juvenile growth over the shelf break than in oceanic waters.